Witnessing Music from the New Wilderness. Issue 3 (3rd May 2016) - Waterman, Ellen
Abstract : In February 2014 the Western Front, a Vancouver-based artist-run centre, produced Music from the New Wilderness, a concert comprising four commissioned works that employed music, archival sound and images of the Thompson Nation, and soundscape recordings of the rainforest coast to explore the geopolitical and environmental history of rural British Columbia. I examine this event in a performance ethnography including close readings of two collaborative works, one by acoustic ecologist Jennifer Schine and composer Adam Basanta, the other by violinist and composer Jesse Zubot and visual artist Krista Belle Stewart. Bearing witness to the entanglement of nature and culture, the artists confront the myth of the sublime wilderness with the realities of human intervention in these works. Music from the New Wilderness offers a provocation to rethink the very concept of wilderness and our relationship to it in terms of Canada's settler history of colonization: its exploitation of both the land and First Peoples.